Analysis of indoor particles and gases and their evolution with natural ventilation. (1st August 2019) - Fortenberry, Claire; Walker, Michael; Dang, Audrey; Loka, Arun; Date, Gauri; Cysneiros de Carvalho, Karolina; Morrison, Glenn; Williams, Brent
Abstract: The air composition and reactivity from outdoor and indoor mixing field campaign was conducted to investigate the impacts of natural ventilation (ie, window opening and closing) on indoor air quality. In this study, a thermal desorption aerosol gas chromatograph (TAG) obtained measurements of indoor particle‐ and gas‐phase semi‐ and intermediately volatile organic compounds both inside and outside a single‐family test home. Together with measurements from a suite of instruments, we use TAG data to evaluate changes in indoor particles and gases at three natural ventilation periods. Positive matrix factorization was performed on TAG and adsorbent tube data to explore five distinct chemical and physical processes occurring in the indoor environment. Outdoor‐to‐indoor transport is observed for sulfate, isoprene epoxydiols, polycyclic aromatic hydrocarbons, and heavy alkanes. Dilution of indoor species is observed for volatile, non‐reactive species including methylcyclohexane and decamethylcyclopentasiloxane. Window opening drives enhanced emissions of semi‐ and intermediately volatile species including TXIB, DEET, diethyl phthalate, and carvone from indoor surfaces. Formation via enhanced oxidation was observed for nonanal and 2‐decanone when outdoor oxidants entered the home. Finally, oxidative depletion of gas‐phase terpenes (eg, limonene and α‐pinene) was anticipated but not observed due to limited measurement resolution and dynamically changing conditions.